Evaluation of endogenous compounds pharmacokinetics as illustrated by calcium - N. N. Eremenko; D. V. Goryachev; E. V. Shikh (Регуляторные исследования и экспертиза лекарственных средств, 2018)
The article reviews scientific literature on the conduct of in vivo pharmacokinetic studies of drugs that are similar to endogenous compounds. It summarises approaches to pharmacokinetic evaluation of calcium drugs. It was demonstrated that the pharmacokinetic evaluation of drugs containing calcium ions in the form of various salts requires assessment of several parameters: parameters indicative of calcium absorption (Cmax and AUC with due regard to baseline concentrations of endogenous calcium), homeostatic mechanisms which regulate the concentration of this endogenous compound (calcium excretion parameters) and hormonal regulation of phosphate and calcium homeostasis (parathyroid hormone).